Gestational Age at Delivery and Neonatal Outcomes among Infants with Gastroschisis in the Children's Hospitals Neonatal Consortium (CHNC) - Riddle, Stefanie; Acharya, Krishna; Agarwal, Nidhi; Ahmad, Irfan; Bendel-Stenzel, Ellen; Shepherd, Jennifer; Williams, Sadie; Zaniletti, Isabella; Jacobson, Elizabeth; the Children's Hospitals Neonatal Consortium's Gastroschisis Focus Group (American Journal of Perinatology, 2022)
Objective The effect of gestational age (GA) on gastroschisis outcomes is unclear and delivery timing varies in practice. We aimed to correlate clinical outcomes of infants with gastroschisis and GA at delivery in the Children's Hospitals Neonatal Consortium (CHNC).Study Design This was a retrospective multicenter cohort study of infants with gastroschisis admitted to CHNC neonatal intensive care units (NICUs) from 2010 to 2016. Patients were categorized by GA: 32 to 346/7, 35 to 366/7, and ≥37 weeks. Respiratory and feeding interventions, mortality, length of stay, and common complications were compared.Results In 2021 for patients with gastroschisis, median GA at delivery was 36.3 weeks (interquartile range [IQR] 35.1, 37.3) and mean birth weight 2,425 g (IQR 2,100, 2,766). Overall mortality was low and there was no difference across GA groups. Infants <35 weeks' gestation had the greatest need for respiratory and feeding interventions. Complications such as medical necrotizing enterocolitis (NEC), cholestasis, and central line-associated blood stream infection were less common in infants ≥37 weeks. Feeding initiation and full feeds were earliest in term infants, compared with infants between 35 and 366/7 weeks, and longest in infants <35 weeks. Prematurity had a significant negative association with breast milk exposure. Enteral feeding tube support at discharge increased with prematurity. Compared with term, infants born between 35 and 366/7 weeks' gestation had a higher incidence of medical NEC and lower exposure to mother's milk at discharge but the need for respiratory interventions or tube feeding at discharge was similar.Conclusion Premature infants with gastroschisis had more neonatal complications including respiratory interventions, longer NICU stay, longer time to full enteral feeds, and higher need for tube feeds at discharge as compared with those delivered at term. Differences were greatest for those <35 weeks GA. While overall mortality remains low, these results provide additional information about GA at birth in gastroschisis, with no evidence of benefit from preterm delivery.Key Points
Keywords: gastroschisis; prematurity; gestational age; Children's Hospitals Neonatal Consortium